2022
DOI: 10.3390/life12050726
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Identifies CCN2 and THBS1 as Biomarker Candidates for Cardiac Hypertrophy

Abstract: Cardiac hypertrophy is a condition that may contribute to the development of heart failure. In this study, we compare the gene-expression patterns of our in vitro stem-cell-based cardiac hypertrophy model with the gene expression of biopsies collected from hypertrophic human hearts. Twenty-five differentially expressed genes (DEGs) from both groups were identified and the expression of selected corresponding secreted proteins were validated using ELISA and Western blot. Several biomarkers, including CCN2, THBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Overexpression of THBS1 (thrombospondinin-1) was shown in literature to have deleterious cardiac effects and its expression was inhibited by RTX. A differential gene expression study 34 identified THBS-1 as a candidate biomarker for cardiac hypertrophy. Moreover, THBS-1 gene was overexpressed in endothelin-stimulated cardiomyocytes, leading to hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of THBS1 (thrombospondinin-1) was shown in literature to have deleterious cardiac effects and its expression was inhibited by RTX. A differential gene expression study 34 identified THBS-1 as a candidate biomarker for cardiac hypertrophy. Moreover, THBS-1 gene was overexpressed in endothelin-stimulated cardiomyocytes, leading to hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Using data mining Johansson et al (2022) identified CCN2 as a putative biomarker of cardiac hypertrophy in an in vitro stem‐cell‐based cardiac hypertrophy model (ET1 utilizing treated human‐induced pluripotent stem‐cell‐derived CMs (hiPSC‐CMs)), compared with the gene expression of biopsies collected from hypertrophic human hearts. Again, analyzing the CCN2 interactome revealed CCN2 as a central node within many biological processes associated with cardiac function and the development of cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%